ASUHAN KEPERAWATAN PADA KELUARGA DENGAN ARTHRITIS REUMATOID (AR) DIKABUPATEN ENDE: - Sekunda, Maria Salestina; Cahyani, Sisilia Leny; Bai, Marieta (Kelimutu Nursing Journal, 2024)
Rheumatoid arthritis is the most common autoimmune disease in the community. It can lead to long-term joint damage, prolonged pain, loss of function and disability (Singh, et al., 2012). This case study aims to enable the author to carry out Nursing Care in the family of Mr. K. S with one of the family members suffering from Rheumatoid Arthritis using the nursing process approach. This case study aims to enable the author to carry out Nursing Care in the family of Mr. K. S with one of the family members suffering from Rheumatoid Arthritis using the nursing process approach. This case study uses a case study method through nursing care steps starting from assessment, nursing diagnosis, intervention, implementation, evaluation to nursing documentation activities. The results of the assessment on the family on behalf of Mrs. K. S complained of pain in the left knee, weak body, swelling in the left knee. The nursing problems raised in these cases are disorders of comfort, pain, and physical mobility inhibitions. The evaluation found that the problem of pain discomfort disorder was partially resolved because the client had shown signs of controlled pain such as a relaxed face, Pain scale 1 (0-10) vital signs within normal limits: and for physical mobility impediments are partially resolved because the client says he can walk on his own even though he still feels a little pain. The problems caused by Rheumatoid Arthritis are very complex and can cause various problems in the human life system, so clients are encouraged to carry out treatment as early as possible, follow the rules of taking medication and implement healthy living behaviors.